(untitled) (Al-Aasar, 2025)
Dr. Muhammad Iqbal is one of the greatest poets of Urdu and Persian. He has written many Urdu and Persian poetry books. Allama Iqbal’s Persian body of poetry has one core element: love or Ishq, which depicts his spirituality and philosophical understanding. Iqbal, both a poet and a philosopher, was a man of vision; he conceptualizes Ishq as a romantic love, rather, as a force that can reach humankind’s fullest potential, raise them spiritually, and create a bond with God. This article looks into the deep and complex images of Ishq by Iqbal, shedding light on the earthly and divine aspects of it. The study illustrates how Iqbal approaches khudi and love as stepping stones to reach the higher realm, and reimagines Ishq as the key to self-realization. He elaborates on Iqbal’s methods and approach by placing him in the dissemination of love by classic poets. This article cites Allama’s brand of mysticism and the connections that Ishq makes in terms of universal spirituality. So, this becomes a testimony to Allama’s exceptional poetics vision and his ability to fuse individualism with universalism. All of his Persian poetry books including “Asrar-e-Khudi”, “Ramooz-e-Be Khudi”, “Piam-e-Mashriq”, “Zaboor-e-Ajam”, “Javed Nama”, “Pass Cheh Bayad Karad Aey Aqwam-e-Mashriq” and “Urmaghan-e-Hijaz” contain numerous verses depicting Iqbal’s clear philosophical views about Ishq.